There are three of us: parents’ experiences of the importance of teacher-student relationships and parental involvement in upper secondary school - Vibeke Krane; Trude Klevan (International Journal of Adolescence and Youth, 2019)
The aim of this study was to obtain parents’ perspectives on the development and importance of teacher-student relationships (TSR) and parental involvement in upper secondary school. The study had a qualitative approach where 14 parents of upper secondary school students were interviewed. The data were analysed via a thematic analysis and organized into three main themes: (1) ‘The multitalented teacher’: mastering school subjects and personal relationships. (2) ‘Parents are responsible’: to support and guide students in teacher-student relationships. (3) ‘Between childhood and adulthood’: students must gradually take on more responsibility. The findings demonstrate that home and school are pivotal contexts in the lives of upper secondary students, and contribute to the development of a tripartite relationship between teacher, student, and parent (TSPR). Parental involvement is described as crucial, especially for students at risk. The study calls for awareness of how positive TSPR in upper secondary school can be developed.